Estado e políticas públicas no mercado de castanha-dobrasil no Estado do Acre: uma análise pela abordagem do desenvolvimento local - Sheila Maria Palza Silva (Revista IDEAS, 2010)
This article aims to discuss the functioning of the nut market in the State of Acre in Brazil based on the approach of local development. For this, we stress the role of social actors involved, the social relations established, and the main problems faced by the market. Highlighting the main programs were developed by the state in recent years, and the effects of these policies to stabilize the income. Examining also how to alter the social relations developed in the nut market in the State of Acre, emphasizing the situation of many families, who have failed to access such programs, and these families consequently have been experiencing social relations of exploitation and dependency in the process of commercialization of Brazil nut.